GRP-147 Pre-Post Study of Interruptions in a Pharmacy Department. (12th March 2013) - Guérin, A; Caron, E; Lebel, D; Bussières, JF
Abstract : Background: Interruptions are a major concern in hospital pharmacy settings, given the nature and the requirements of the work such as sustained focused attention, validating prescriptions and performing complex processes. Interruptions may jeopardise the safe delivery of pharmaceutical services. Purpose: The primary objective was to compare the number of stimuli per hour received and made by pharmacists and pharmacy technicians between 2010 and 2012. The secondary objective was to evaluate the impact of five corrective measures. Materials and Methods: This was a pre-post cross-sectional observational study. The study was conducted in the main dispensing area of the pharmacy department of a University Hospital Center. The area is composed of three data entry stations each assigned one pharmacist and one pharmacy technician. Stimuli received and made by pharmacists and pharmacy technicians were counted before (2010) and after (2012) the implementation of corrective measures. The effect of five corrective measures was measured with a t-test for targeted stimuli. Results: Sixty-two random 30-minute observation periods in 2010 (n = 2, 663 stimuli) and 31 periods in 2012 (n = 1, 217 stimuli) were conducted. An average rate of 85.9 ± 22.2 stimuli per hour was calculated in 2010 vs. 78.52 ± 20.1 in 2012 (P = 0.06). We observed a statistically significant decrease in the mean rate of stimuli per hour for three types of stimulus for pharmacists (i.e. printer noise 3.7 ± 2.4 vs. 0.6 ± 1.8 p < 0.001, face-to-face non-professional conversations 4.4 ± 4.2 vs. 1.2 ± 1.8 p = 0.003, Web browsing 1.3 ± 2.2 vs. 0 ± 0 p = 0.009) and for one type of stimuli for pharmacy technicians (i.e. printer noise 4.7 ± 3.2 vs. 0.75 ± 1.8 p < 0.001). Conclusions: Despite the corrective measures, there was no statistically significant difference between the rates of stimuli per hour observed in 2010 and 2012. Other studies are needed to identify more efficient corrective measures and to better describe the nature and the impact of stimuli, distractions and interruptions in pharmacy practise. No conflict of interest.